2019
DOI: 10.1016/j.enmm.2019.100266
|View full text |Cite
|
Sign up to set email alerts
|

Clay minerals for the removal of pharmaceuticals: Initial investigations of their adsorption properties in real wastewater effluents

Abstract: The adsorption of pharmaceutical products (PPs) onto kaolinite and raw and sodium-exchanged montmorillonite was investigated in real wastewater effluents (WWE). The important role of the charge state of the PPs in controlling the adsorption extent was highlighted. Whereas cationic PPs were mostly adsorbed through cation exchange, the adsorption of neutral and anionic PPs appeared to be controlled by the nature of compensating inorganic cations and/or the simultaneous adsorption of organic moieties onto clay mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, clay minerals could be inexpensive and widely available materials for the removal of pharmaceuticals [82]. For clay materials, the most common types (illite, kaolinite, vermiculite, montmo-rillonite, bentonite, and sepiolite) have already been used for the removal of a variety of organic micro-pollutants.…”
Section: Claysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clay minerals could be inexpensive and widely available materials for the removal of pharmaceuticals [82]. For clay materials, the most common types (illite, kaolinite, vermiculite, montmo-rillonite, bentonite, and sepiolite) have already been used for the removal of a variety of organic micro-pollutants.…”
Section: Claysmentioning
confidence: 99%
“…For clay materials, the most common types (illite, kaolinite, vermiculite, montmo-rillonite, bentonite, and sepiolite) have already been used for the removal of a variety of organic micro-pollutants. Montmorillonite is the most promising adsorbent for further investigations aimed at testing the practicability of a clay-based adsorbent for the removal of pharmaceuticals compounds [82]. The use of natural clay (montmorillonite (Mt), vermiculite (VER), bentonite (B), kaolinite (K)) and modified clay-based sorbents commercial acid-activated montmorillonites K10 and K30, and two carbonaceous-mineral nanocomposites (MtG5%T, BAlG3%C) for the removal of ibuprofen, diclofenac, ketoprofen, carbamazepine, bisphenol A, and triclosan, showed that vermiculite was the best adsorbent for the removal of all drugs.…”
Section: Claysmentioning
confidence: 99%
“…Adsorption of carbamazepine on various clays was examined in several studies. Adsorption studies on montmorillonite are inconclusive, while some studies present poor-to-low adsorption capacities (0-0.02 mmol g −1 ) [35][36][37][38] and others report considerably higher values (up to 0.15 mmol g −1 ) [39,40]. Most studies have ascribed adsorption of CBZ on montmorillonite to Van der Waals interactions between the aromatic rings and the clay surface, and hydrogen bonds coordinating between oxygen atoms and exchangeable cations [36,38,40].…”
Section: Introductionmentioning
confidence: 99%
“…To ease the recovery of used adsorbents, they can be made responsive to an applied magnetic field, as it was successfully demonstrated with carbon nanotubes impregnated with a metal phase [ 27 ]. Adsorbents based on clay minerals [ 28 ] have also been considered as readily available natural materials that can be used to remove organic micropollutants [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%